Implementing Privacy-First Architecture: A Technical Guide to Ethical Data Pipelines and AI Systems - Amber Chowdhary, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive technical article explores the implementation of privacy-first architecture in modern data pipelines and AI systems, addressing the critical intersection of privacy, ethics, and technological advancement. The article presents a detailed framework for organizations to develop and maintain secure, ethical, and compliant data processing systems while ensuring operational efficiency. It examines the evolution of data protection infrastructure, including advanced anonymization techniques, encryption protocols, and access control systems. The article delves into ethical AI development principles, emphasizing fair and transparent model development, comprehensive testing protocols, and sophisticated bias detection mechanisms. Furthermore, it addresses regulatory compliance implementation, focusing on GDPR and CCPA requirements, and explores the maturation of governance frameworks and oversight mechanisms. The article also discusses the critical aspects of team development, security awareness, and stakeholder management in maintaining effective privacy-first systems. Through an article analysis of modern technical architectures and integration patterns, this work provides organizations with actionable insights for implementing robust privacy-first solutions that can adapt to evolving technological landscapes and security challenges.
Keywords: Privacy-First Architecture; Ethical AI Development; Data Protection Infrastructure; Regulatory Compliance; Governance Framework